Is there a financial incentive to immigrate? Examining of the health worker salary gap between India and popular destination countries - Gavin George; Bruce Rhodes (BMC, 2017)
Abstract Background International migration is one of the factors resulting in the shortage of Human Resources for Health (HRH) in India. Literature suggests that migration is fuelled by the prospect of higher salaries available abroad. The extent of these salary differentials are unknown, and this study seeks to examine the salaries of selected HRH in India and four popular destination countries (United States of America, United Kingdom, Canada and the United Arab Emirates), whilst accounting for the in-country cost of living. This study will therefore determine truer financial incentives for Indian HRH to migrate abroad. Methods A purchasing power parity (PPP) ratio is employed to equalise the international price of buying a representative basket of commonly bought goods (including food, entertainment, fuel and utilities). Using the PPP index, real differences in salaries are directly compared for selected work categories and different levels of work experience in the four respective countries. Results Nurses in the USA can earn up to 82.7% more than their Indian counterparts. Nurses in Canada and the UAE reveal more modest salary differentials, yet still significant better off by up to 28 and 20% respectively. Only nurses in the UK are potentially materially worse off than nurses working in India. We observe significant potential PPP gains of up to 57.4, 99.1 and 94.4% for medical doctors in the USA, Canada and the UAE respectively. Medical specialists potentially experience the greatest income disparities with anaesthetists potentially earning up to 600% more than their counterparts in India. Radiologists operating in the UK and general surgeons working in the USA can potentially earn more than double that of their counterparts working in India. We observe more modest positive or negligible PPP gains in other selected countries for health specialists. Conclusion Even when considering the differences in the cost of living, the financial incentive for selected cadres of Indian HRH to seek work abroad remains strong. The migration of Indian HRH to countries offering superior salaries makes it difficult for India to retain experienced health personal and compromises government efforts to render health care more accessible across the country.